A SPACE-TIME SCAN STATISTIC TO DETECT CLUSTER ALARMS OF DENGUE MORTALITY IN INDONESIA, 2005 - Widyaningsih, Yekti; Pin, Tjiong Giok (UI Scholars Hub, 2018)
This article presents a space-time scan statistic, useful for evaluating space-time cluster alarms, and illustrates the method to investigate a recent dengue mortality alarm in Indonesia. Space-time scan statistics account for multiple testing inherent in a cluster alarm. The baseline process may be any inhomogeneous Poisson process with intensity proportional to some known function. Confounders in a particular time can be adjusted for. Three cluster alarms of dengue mortality in Indonesia in 2005 were statistically significant. Space-time scan statistics are useful as screening tools for evaluating which cluster alarms merit further investigation and which clusters are probably chance occurrences.